Assessing the role of eosinophil‐mediated immune response markers in detecting hookworm infection: A case‐control study in Kintampo, Ghana. Issue 4 (3rd June 2022) - Sakyi, Samuel A.; Amoani, Benjamin; Opoku, Stephen; Dzata, Lawrence; Aniagyei, Wilfred; Senu, Ebenezer; Dankwa, Kwabena; Wilson, Michael D.
Abstract: Background and Aim: Human hookworm disease caused by Ancylostoma duodenale and Necator americanus is a serious public health problem. Hookworm infection activates eosinophil‐mediated tissue inflammatory responses, involving the production of the eosinophil‐specific chemokine (eotaxin), recruitment of eosinophils, secretion of the cationic protein, and production of antiparasite immunoglobulin E (IgE). We investigated eosinophil‐mediated immune response as markers (CCL11,  eosinophil cationic protein [ECP], and IgE) for detecting hookworm infection. Methods: This case‐control study was carried out in hookworm endemic areas within the Kintampo North Municipality.Forty hookworm‐positive subjects and 36 apparently healthy individuals were recruited as cases and controls, respectively. Stool samples were collected for hookworm detection by the Kato–Katz technique and speciation by polymerase chain reaction. Approximately, 5 ml of intravenous blood was used to obtain plasma for the immunological assays. Results: Of eosinophil‐mediated immune response markers studied, ECP and CCL11 were significantly higher among hookworm patients compared to controls. Increasing CCL11 ( β  = −0.81, p  = 0.015) was associated with a significant decrease hookworm intensity. However, increasing eosinophil count ( β  = 0.62, p  = 0.027) was associated with significant increase in hookworm intensity. In receiver operator characteristics analysis, ECP could significantly detect hookworm infection with a very high area under the curve (AUC) (AUC = 0.97, p  < 0.0001). At a cutoff of 39.05, ECP was the best eosinophil‐mediated immune response marker for detecting hookworm infection with a sensitivity of 97.2%, specificity of 87.8%, a positive predictive value of 89.7%, and a negative predictive value of 96.6%. Conclusion: ECP best predicts eosinophil‐mediated immune response for detecting hookworm infection, while CCL11 and eosinophil count better predict the intensity of hookworm. Moreover, the ECP level is a good indicator of hookworm infection and intensity and may require additional investigations to augment current hookworm diagnostic techniques.